DNA barcoding for elasmobranch diversity assessment in Thailand: Its advantages and limitations - Jenjit Khudamrongsawat; Tassapon Krajangdara; Thadsin Panithanarak; Ratima Karuwancharoen; Wanlada Klangnurak; Pattarapon Promnun; Wansuk Senanan (PLoS ONE, 2025)
The assessment of elasmobranch biodiversity in Thailand benefits greatly from the application of DNA barcoding, which helps mitigate the challenge posed by a shortage of expert taxonomists. Fragments of COI and ND2 mitochondrial DNA were examined, and the strengths and weaknesses of these two markers were compared. In this study, DNA products from 153 elasmobranch samples were amplifiable and revealed a total of 28 shark species and 32 batoid species. Many species could be confidently identified as their morphological characteristics aligned with DNA barcodes. However, several exceptions were recognized. The absence of reference sequences for rare species presented a challenge for species verification, and the misidentification of reference sequences, as well as changes in species names due to taxonomic revisions, added complexity when comparing DNA barcoding sequences. Conflicts between morphology and genetics were also observed. While intraspecific genetic variation based on both DNA barcodes generally indicated 0–2% variation, this metric could not always be used for species delimitation. This was particularly true for species displaying low genetic variation among closely related species and species where cryptic diversity remained hidden and yet to be uncovered. In such cases, the morphological characteristics of the samples served as the primary means of species identification. Despite these challenges, DNA barcoding remains an invaluable tool for biodiversity assessment, especially in light of the shortage of skilled experts, and for identification of products made from vulnerable species. However, it is essential to exercise caution and be aware of these complexities in its application.